Successful sequential immune epigenetic therapy of erythrodermic mycosis fungoidesessful sequential immune epigenetic therapy with the resistant course of erythrodermic mycosis fungoides - L. G. Gorenkova; S. K. Kravchenko; A. M. Kovrigina; O. A. Kolomeitsev (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Mucosis fungoidea (МF) belongs to the class of epidermotropic T-cell lymphomas. MF is represented by over 10 sub-types only in terms of its clinical manifestations, with one of them being erythrodermic MF (EMF). This disease is characterized by diverse symptomatology in the form of erythroderma and intense skin itch, aggressive сlinical course and unfavorable prognosis. The disease prognosis also correlates with age, previous history of long-term systemic gluco-corticosteroid treatment (GCS), increased activity of lactate dehydrogenase (LDH) and hypereosinophilia. The choice of MF treatment is determined by the disease stage and somatic status of the patient. In EMF, a therapy combining various effective preparations and taking into account the specifics of the given case is required. Extracorporeal photopheresis (ECP) is frequently an approach of choice; however, it has demonstrated the highest efficacy in Sezary disease or in EFM associated with leucemization. Application of new pharmaceuticals (monoclonal antibodies, epigenetic agents) in combination or in sequence with immune therapy is a promising direction, particularly for treating patients older than 75 years. In this paper, we describe the clinical case of an elderly patient suffering from EMF without peripheral blood leukemia with multimodal factors of unfavorable prognosis, such as age, increased lactate dehy drogenase activity, history of prolonged inefficient treatment with gluco-cortecosteroid preparations and eosinophilia. A long-term positive response to the treatment using sequential immune epigenetic therapy has not been achieved, although the treatment tolerability and the patient's life quality were satisfactory.